Exercise Timing Influences Autonomic and Psychological Adaptations but not Functional Capacity in Cancer Patients Undergoing Treatment - Buck W. Covington II; Brooke Mattocks; Luke Krynski; Lea Haverbeck Simon; Jesse Hayward; Melissa Villafana; Mike Lazio; Reid Hayward (Medicine & Science in Sports & Exercise, 2026)
Purpose: To examine the effects of exercise timing (morning [AX] vs evening [PX]) on functional capacity, psychological outcomes, and sleep-related measures in cancer patients undergoing treatment. Methods: Forty-four cancer patients undergoing treatment participated in a supervised exercise intervention at the University of Northern Colorado Cancer Rehabilitation Institute (UNCCRI). Participants self-selected exercise timing as AX (0700–0900) or PX (1600–1800) and completed a range of pre- and post-intervention physical and psychological assessments. A subset of participants (n=24) completed objective sleep and recovery monitoring using a wearable tracker. Results: Both AX and PX groups demonstrated significant improvements in functional capacity, with no significant differences between groups for these variables (p > 0.05). In contrast, exercise timing was associated with significant differences in psychological and autonomic outcomes. The AX group demonstrated greater reductions in Beck Depression scores (-4.86 ± 5.72 vs -1.02 ± 4.48; p < 0.05) and greater improvements in PSQI scores (-3.76 ± 3.39 vs 0.08 ± 1.83; p < 0.001) compared to the PX group. The AX group exhibited a substantially greater increase in heart rate variability (8.01 ± 6.31 ms) compared to a decrease in the PX group (-4.49 ± 6.79 ms; p < 0.001), representing a marked divergence in autonomic adaptation between groups. These differences were supported by moderate-to-large to very large effect sizes, indicating clinically relevant improvements in autonomic and psychological outcomes. No other objective sleep variables differed significantly between groups. Conclusions: A 12-week supervised exercise intervention improved functional capacity in cancer patients undergoing treatment, independent of exercise timing. However, morning exercise was associated with greater improvements in autonomic function, sleep quality, and depressive symptoms compared to afternoon/evening exercise.